Comparison between two optimization strategies for Solid Oxide Fuel Cell-Gas Turbine hybrid cycles - Zhao,Y; Shah,N; Brandon,NP (International Journal of Hydrogen Energy, 2011)
This paper compares the performance characteristics of a combined power system with solid oxide fuel cell (SOFC) and gas turbine (GT) working under two thermodynamic optimization strategies. Expressions of the optimized power output and efficiency for both the subsystems and the SOFC-GT hybrid cycle are derived. Optimal performance characteristics are discussed and compared in detail through a parametric analysis to evaluate the impact of multi-irreversibilities that take into account on the system behaviour. It is found that there exist certain new optimum criteria for some important design and operating parameters. Engineers should find the methodologies developed in this paper useful in the optimal design and practical operation of complex hybrid fuel cell power plants.